Glycans as Modulators of Plant Defense Against Filamentous Pathogens - Chaliha, Chayanika; Rugen, Michael D.; Field, Robert A.; Kalita, Eeshan (Frontiers in Plant Science, 2018)
Plants and microbes utilize glycoconjugates as structural entities, energy reserves for cellular processes and components of cellular recognition or binding events. The structural heterogeneity of carbohydrates in such systems is a result of the ability of the carbohydrate biosynthetic enzymes to reorient sugar monomers in a variety of forms, generating highly complex, linear, branched or hierarchical structures. During the interaction between plants and their microbial pathogens, the microbial cell surface glycans, cell wall derived glycans and glycoproteins stimulate the signaling cascades of plant immune responses, through a series of specific or broad spectrum recognition events. The microbial glycan-induced plant immune responses and the downstream modifications observed in host-plant glycan structures that combat the microbial attack have garnered immense interest among scientists in recent times. This has been enabled by technological advancements in the field of glycobiology, making it possible to study the ongoing co-evolution of the microbial and the corresponding host glycan structures, in greater detail. The new glycan analogues emerging in this evolutionary arms race brings about a fresh perspective to our understanding of plant-pathogen interactions. This review discusses the role of diverse classes of glycans and their derivatives including simple sugars, oligosaccharides, glycoproteins and glycolipids in relation to the activation of classical PTI (Pattern-Triggered Immunity) and ETI (Effector-Triggered Immunity) defense responses in plants. While primarily encompassing the biological roles of glycans in modulating plant defense responses this review categorizes glycans based on their structure thereby enabling parallels to be drawn to other areas of glycobiology. Further, we examine how these molecules are currently being used to develop new bio-active molecules, potent as priming agents to stimulate plant defense response and as templates for designing environmentally friendly foliar sprays for plant protection.